IMPLEMENTASI REFORMASI BIROKRASI TERHADAP KINERJA KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) SURABAYA I - Rizka, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to know and analyze the performance of Government Treasury Office Surabaya I by using Regulations of Ministry for State Apparatus Reforms and Bureaucracy Reformation Republic of Indonesia No. 38 in 2012 about The foundation of performance appraisal in Public service unit as benchmarks to asses the performance levels, with the component of vision appraisal, mission, and service motto; service standard and intimation service; system, mechanism, and service procedure; Human Resources, facility and infrastructure service, complaint handling; Public Satisfy Index; Public Service of the information system; and productivity in reaching the service target. The research samples is the employees of Government Treasury Office Surabaya I with the number of respondent is 25 people. The data collection technique in this research is using documentation, interview, and questioner. Meanwhile, the data analysis technique is using qualitative descriptive method. The research result shows that the performance of State Treasury Office Surabaya I can be said good or already optimum because the performance value is close to the appraisal maximum value of 807, where the appraisal maximum value as the foundation of performance appraisal in public service unit is 1000. If itâs percentage, the performance of State Treasury Office Surabaya Iis 80.7%Keywords: The Performance, Public service, bureaucratic reform